‘Moving and Meeting’ to Action: Who Can Create Momentum to Support Refugees in Europe? - Schulz, Olivia (Satura, 2024)
In 2015, when large numbers of people began fleeing war in Syria, former German Chancellor Angela Merkel claimed that she would allow a million refugees into her country, uttering the much debated words “Wir schaffen das!” (We can do this!”). Politicians faced many dilemmas in 2015 and all across Europe, policy makers eventually admitted to having made mistakes. Addressing new challenges and past failures, European Commissioner for Home Affairs Ylva Johansson told the press in March 2022, that politicians have learned lessons from their mistakes. It can thus be assumed that this time in Europe “we can do this better” with the millions of Ukrainian refugees, possibly with the help of civil society again. It is in fact civil society that is often anxious to maintain the momentum of the search for sustainable solutions for refugees. This paper closely examines the local voluntary association ‘Move and Meet’ that was originally founded in 2016 in Münster, Germany, soon after the 2015 refugee crisis to support and include female migrants through physical activity into society. It will be argued that for the new wave that includes mostly Ukrainian women, it is beneficial to look at successful examples of civil society initiatives that were established to help female migrants who arrived to Europe in 2015. It is through these players that the game’s momentum can be kept up so that politicians this time may exclaim: “We can win this!”.